Purification and characterization of α-glucosidase from Penicillium chrysogenum. - Hamed M El-Shora,; Saida M Messgo,; Mohsen E. Ibrahim,; Mohamed W alfakharany, (International Journal of Phytomedicine, 2018)
α-glucosidase (EC: 3.2.1.20) was isolated and purified from Penicillium chrysogenum Thom ATCC 10106 by ammonium sulphate precipitation (75%), DEAE-cellulose and Sephadex G-200. The specific activity was 140 units (U) mg-1 protein. The enzyme expressed a single band using SDS-PAGE and the molecular weight of the enzyme was nearly 43KDa. The optimal pH and temperature were 8 and 40ºC. The activation energy was 17.94 k J mol-1. The optimal incubation time was 40 min. Glutamine, glutamic acid, cysteine, alanine, phenylalanine, glycine, methionine, asparagine enhanced the enzyme activity and cysteine was the best enhancer. However, cystine and arginine inhibited α-glucosidase activity. The Vmax values were 48 and 38.1 U mg-1 protein with and without of cysteine, respectively. However, Km values were 0.21 and 0.25 mM in absence and presence of cysteine, respectively.